2005
DOI: 10.1007/s00251-004-0756-0
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II alleles and measles virus-specific cytokine immune response following two doses of measles vaccine

Abstract: Measles virus-specific T cells and the production of cytokines play a critical role in the immune response following measles immunization. To understand the genetic factors that influence variation in IFN-gamma and IL-4 responses following measles immunization and to provide insight into the factors influencing both cellular and humoral immunity to measles, we assessed associations between human leukocyte antigen (HLA) class II genes and measles-specific Th1 and Th2-type cytokine responses in peripheral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…Likewise, class II HLA-DRB1 (*0301, *0901 and *1501) and DRB1 (*0103, *0701 and *1101) alleles were associated with IFN-γ and IL-4 secretion, respectively. In addition, the DQB1 alleles with an association with IFN-γ secretion were *0201, *0303, *0402 and *0602 [26]. These previous studies could not rule out the role of other cytokines, including IL-2, IL-10 and IL-12, associated with HLA complex since they were not studied.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Likewise, class II HLA-DRB1 (*0301, *0901 and *1501) and DRB1 (*0103, *0701 and *1101) alleles were associated with IFN-γ and IL-4 secretion, respectively. In addition, the DQB1 alleles with an association with IFN-γ secretion were *0201, *0303, *0402 and *0602 [26]. These previous studies could not rule out the role of other cytokines, including IL-2, IL-10 and IL-12, associated with HLA complex since they were not studied.…”
Section: Discussionmentioning
confidence: 89%
“…Prior population-based studies found associations with both class I and class II alleles and measles vaccine immune response [22][23][24]. Subsequent studies suggest the significance of HLA genes in measles virus-specific IFN-γ and IL-4 cytokine immune responses [25,26]. The class I HLA-A (*0101 and *3101) and HLA-Cw (*0303 and *0501) alleles have been significantly associated with measles virus-induced IFN-γ secretion [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations